2016
DOI: 10.1002/ar.23331
|View full text |Cite
|
Sign up to set email alerts
|

The Skull of Phyllomedusa sauvagii (Anura, Hylidae)

Abstract: The hylid genus Phyllomedusa comprises charismatic frogs commonly known as monkey, leaf or green frogs, and is the most diverse genus of the subfamily Phyllomedusinae, including about 31 species. Although there is some information about the anatomy of these frogs, little is known about the osteology. Here the adult skull of Phyllomedusa sauvagii, both articulated and disarticulated, is described and the intraspecific variation is reported. Additionally, cartilage associated with the adult skull, such as the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The anterior end of the quadratojugale appear pointed and chamfered in place of contact with maxillare . For example, a similar junction of maxillare and quadratojugale was found in Phyllomedussa sauvagii (Anura, Hylidae), but in these frogs the extent of contact region of these bones varies from 1/3 to 1/2 of the length of quadratojugale (Ruiz-Monachesi M. R. et al, 2016). In late Cretaceous anuran Hungarobatrachus szukacsi Szentesi & Venczel, 2010 was found that dorsolingual surface of posterior part of maxillare had a shallow, triangular facet for contact with the quadratojugale (Venczel M. et al, 2021).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The anterior end of the quadratojugale appear pointed and chamfered in place of contact with maxillare . For example, a similar junction of maxillare and quadratojugale was found in Phyllomedussa sauvagii (Anura, Hylidae), but in these frogs the extent of contact region of these bones varies from 1/3 to 1/2 of the length of quadratojugale (Ruiz-Monachesi M. R. et al, 2016). In late Cretaceous anuran Hungarobatrachus szukacsi Szentesi & Venczel, 2010 was found that dorsolingual surface of posterior part of maxillare had a shallow, triangular facet for contact with the quadratojugale (Venczel M. et al, 2021).…”
Section: Resultsmentioning
confidence: 67%
“…Dentale reduced in frogs for example as in Phyllomedusa sauvagii (Anura, Hylidae) (Ruiz-Monachesi M. R. et al, 2016). We found that in studied representatives of the genus Pelophylax dentale had undergone reduction too.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhinella sp. Phyllomedusa is small, short, compressed, and close to semi-spherical in shape (Ruiz-Monachesi et al, 2016), unlike that of MMSCM 2027 which is trapezoidal as commonly observed in Leptodactylus and Rhinella, although shorter in the former (Perotti, 2001;Ponssa, 2006). The deep and open anterior Meckelian groove of the fossil is different form the sutured or fused to the dentary present in most Ceratophryidae (Gómez & Turazzini, 2021).…”
Section: Systematic Paleontologymentioning
confidence: 87%
“…Entre los cuales se incluyen la morfología del esqueleto con la descripción de los elementos del cráneo y poscráneo. En el caso de los anfibios, las descripciones del esqueleto se han enfocado principalmente al estudio del cráneo en adultos (Fabrezi et al, 2016;Ruiz-Monachesi et al, 2016;Caminer y Ron, 2014;De Sá y Hill, 1998;Maglia y Pugener, 1998;Wild, 1997).…”
Section: El Esqueletounclassified